Australian & Indonesian Regulations: Preventive and Repressive Law Enforcement of Consumer Protection in Electronic Commerce: Ni Putu Adhya Pradnyaswari (Focus Journal : Law Review, 2026)
Preventive and repressive consumer protection law enforcement is implemented in Australia and Indonesia. Regulations related to legal protection for consumers in electronic transactions or e-commerce in Australia and Indonesia share significant similarities, with the same principled goal of providing legal protection. However, in Australia, this is regulated by the Australian Consumer Law (ACL), which is part of the Competition and Consumer Act 2010. In Indonesia, consumer protection is regulated by Law Number 8 of 1999 concerning Consumer Protection (UUPK), despite the differences in the legal systems of Australia and Indonesia. The purpose of this study is to analyze and examine the legal comparison between regulations related to legal protection for consumers in electronic transactions or e-commerce in Australia and Indonesia, focusing on the nature of preventive and repressive law enforcement. The research method used in this study is a normative legal research method using a comparative legal approach. The results of the study show that consumer protection laws in Australia and Indonesia, namely in Australia using a single national regulation that regulates consumer protection and business competition in an integrated manner, so that it is more efficient and coordinated, while in Indonesia the regulations are scattered across various regulations that often overlap with many regulations, causing weak effectiveness of supervision and implementation of consumer protection in the e-commerce sector. Furthermore, there are similarities, namely prohibiting misleading practices including fraud and guaranteeing consumer rights, as well as emphasizing that business actors are obliged to be responsible if there is a loss to consumers.